PEMETAAN ATRAKSI WISATA DENGAN MENGGUNAKAN SIG DI DESA WISATA DURENSARI KABUPATEN TRENGGALEK - Bagas Aryaseta; Wahyuni Wahyuni; Lia Nirawati (LPPM Universitas Bina Bangsa, 2023)
Durensari Tourism Village in Sawahan Village, Watulimo District, Trenggalek has a lot of tourism potential. Currently, the village community only focuses on river tourism, but actually there are many other tourist attractions in the village. The UPN Veteran East Java community service team held training and simulations of tourist attractions using GIS (Geographic Information System). With GIS technology, it is hoped that we can analyze the spatial aspects of an area to develop tourism potential into an object with optimal attraction so that it can attract the attention of both domestic and foreign tourists. Apart from that, more tourist attractions will help managers in compiling tour package service products. Based on the results of identifying tourist attractions in Durensari Sawahan Tourism Village, there are 3 types of tourist attractions in Durensari Village, namely Natural Tourism Attractions, Cultural Tourism Attractions, and Artificial Tourist Attractions. After conducting field visits, 10 new tourist attraction locations were identified which were then mapped using GIS technology. The next step is to increase participation from Pokdarwis Durensari members in managing tourism potential to become a tourist attraction which is then packaged in the form of tour packages that can be offered to tourists. The variety of existing tourist attractions can be an opportunity and strength for the Durensari Tourism Village to attract tourist visits